2021
DOI: 10.1111/jdi.13692
|View full text |Cite
|
Sign up to set email alerts
|

Fasting plasma glucose level in the range of 90–99 mg/dL and the risk of the onset of type 2 diabetes: Population‐based Panasonic cohort study 2

Abstract: Aim/Introduction As the association between a fasting glucose concentration of 90–99 mg/dL and the onset of type 2 diabetes is still controversial, we aimed to assess it in 37,148 Japanese individuals with a normal plasma glucose concentration. Materials and Methods This long‐term retrospective cohort study included individuals having a medical checkup at Panasonic Corporation from 2008 to 2018. In total, 1,028 participants developed type 2 diabetes. Results Cox regression analyses revealed that the risk for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Previous studies involving various populations exhibited similar results [ 11 21 ]. Tirosh et al [ 19 ] reported an increased risk of T2D when FPG rose 87 mg/dL (4.83 mmol/L) in a group of 13 163 men aged 26–45 years tested at the Israeli Ministry of Defense Medical Examination Centre.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Previous studies involving various populations exhibited similar results [ 11 21 ]. Tirosh et al [ 19 ] reported an increased risk of T2D when FPG rose 87 mg/dL (4.83 mmol/L) in a group of 13 163 men aged 26–45 years tested at the Israeli Ministry of Defense Medical Examination Centre.…”
Section: Discussionsupporting
confidence: 75%
“…However, the relationship between FPG 90–99 mg/dL (5–5.5 mmol/L) and T2D is controversial. Munekawa et al [ 21 ] suggested that this could be attributed to distinct ages or populations. Consequently, in 2021, they confirmed that FPG 90–99 mg/dL (5–5.5 mmol/L) is associated with an increased risk of T2D using adult physical examination data from the Matsushita cohort in Japan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chun et al determined through univariate and multivariate regression analyses that the risk factors for NODAP include FPG level ≥ 100 mg/dL, TG level ≥ 150 mg/dL, high body mass index (BMI), and highintensity statins and that FPG is more influential than other factors 6 . FPG levels are significantly associated with the risk of diabetes 20 , and each 1 mg/dL increase in FPG leads to a 9% increase in the risk of diabetes, not only in patients with impaired fasting glucose, but also even in patients with normal FPG levels (90-99 mg/dL) 21 . 2 h postprandial glucose (2hPG) is also an indicator for detecting blood glucose levels, but studies have shown that the inclusion of 2hPG and insulin resistance in the prediction model did not significantly improve the predictive www.nature.com/scientificreports/ accuracy of the model 22,23 , and therefore NODAP risk prediction by incorporating a convenient and economical FPG is reliable and practical.…”
Section: Discussionmentioning
confidence: 99%
“…It is a potential target to enhance clinical outcomes in hospitalized patients with acute disease, even without overt diabetes [ 5 ]. It has been suggested that each 1 mg/ dL increment in fasting glucose concentration may increase the risk of developing diabetes by 9% [ 6 ].…”
Section: Introductionmentioning
confidence: 99%